Design and Development of an E-Commerce System at PT. KMK Global Sport - Wau, Laskar Kristiawan; Sharyanto, Sharyanto; Whendasmoro, Raditya Galih (Yayasan Bina Internusa Mabarindo, 2025)
The rapid development of information technology has encouraged companies to adopt digital systems in supporting business processes, including sales. PT. KMK Global Sport, a producer of Nike shoes, faces challenges in expanding its market due to the lack of an integrated e-commerce platform. This study aims to design and develop a web-based e-commerce system that facilitates online sales, integrates inventory and sales data, and ensures transaction security. The research method includes observation, interviews, literature study, and system design using Unified Modeling Language (UML). The system is tested using Black Box Testing. The results indicate that the system successfully supports online sales processes, improves operational efficiency, and enhances data security.